[OP.6B.02] PHENOTYPES OF OFFICE SYSTOLIC BLOOD PRESSURE ACCORDING TO BOTH BRACHIAL AND AORTIC MEASUREMENTS: FREQUENCIES AND ASSOCIATIONS WITH CAROTID HYPERTROPHY IN 1861 ADULTS. (September 2016) - ATHANASE, P.; Protogerou, A.T.; Aissopou, E.; Argyris, A.; Nasothimiou, E.; Konstantonis, G.; Papaioannou, T.; Blacher, J.; Safar, M.; Sfikakis, P.
Abstract : Objective: Aortic (a) systolic blood pressure (SBP) is associated with arterial damage more consistently than brachial (b) SBP. However, it is unknown whether: (i) aSBP is normal in the presence of elevated bSBP, and vice versa; (ii) SBP classification on the basis of proposed bSBP and aSBP cut-off values, improves cardiovascular (CV) risk assessment. We tested (i) the frequency of 4 office SBP phenotypes: type I (both normal bSBP and aSBP); type II (high bSBP but normal aSBP); type III (normal bSBP but high aSBP), and type IV (both high bSBP and aSBP), (ii) the probability of each phenotype (using type I as reference) to be associated with increased arterial damage. Design and method: In a cohort study of 1861 participants (age: years 54 years, 49.1% males), we measured simultaneously bSBP, aSBP and carotid cross-sectional wall area (CSWA) with ultrasound. Results: Depending on the applied aSBP cut-off values, type II and type III phenotypes represented together 5–11 % of the studied population (0.9–3.4% and 1.8–10.3%, respectively). Subgroups with phenotypes II and III had significantly higher probability (by 2.3–3.3 and 3.3–8.9 times, respectively) as assessed by logistic regression analysis to present elevated carotid artery CSWA compared to the reference group, even after adjustment for diastolic blood pressure and other confounders. Conclusions: Defined on the basis of both bSBP and aSBP measurements, type II (i.e. isolated high bSBP) and type III (isolated high aSBP) are commonly observed and refine the detection of subgroups regarding the presence of arterial damage.